Scarcity of Barley and Cotton Cultivation in Kirkuk Governorate (A Community Study) - Abid, Layla Ali; Omar, Mohammed Yashar; Ibrahim, Hashim Mohammed (American Journal of Botany and Bioengineering, 2026)
The relationship between population growth and the possibility of achieving food security—especially under the conditions of climate extremism, tense political relations between countries, technological progress, and the disparity in the population pyramid between the working and non-working groups—makes agriculture at the forefront of the economic sectors that the state seeks to study and prioritize in both its branches (plant and animal) and find appropriate solutions for its problems. Among the most prominent problems affecting the agricultural community in Kirkuk Governorate is the scarcity of barley and cotton cultivation, particularly after the increase in barley imports from neighboring countries, namely Turkey and Iran, and the closure of the cotton gin in the governorate. Therefore, we studied in the first section the geographical distribution of barley and cotton crops in the governorate and the possibility of representing this through maps using the Geographic Information Systems program (ArcView GIS 10.8.2). The second section focused on explaining the most significant reasons that led to the decline in productivity and the rate of change occurring during the period (2012–2022) and the recession of agricultural lands compared to other crops. As for the third section, it addressed providing the most important proposed solutions through which productivity can be increased, representing this with graphs using Excel, and stating conclusions and recommendations, along with mentioning the sources and the appendix (the questionnaire form) adopted in the study.